Bundling Human Capital with Organizational Context: The Impact of International Assignment Experience on Multinational Firm Performance and CEO Pay - Carpenter, Mason A.; Sanders, Wm. Gerard; Gregersen, Hal B. (Academy of Management Journal, 2001)
We develop resource- and dynamic capability-based arguments that CEOs with international assignment experience create value for their firms and themselves through their control of a valuable, rare, and inimitable resource. Supporting this view, U.S. multinationals performed better with CEOs with international assignment experience at their helms, especially when such human capital was bundled with other organizational resources and capabilities. Moreover, in highly global firms, CEOs with international assignment experience appropriated a greater proportion of performance in their pay.